2021
DOI: 10.3389/fmed.2021.747098
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Autoimmune Diseases in Patients With Interstitial Cystitis/Bladder Pain Syndrome: A Nationwide Population-Based Study in Taiwan

Abstract: Objective: The association between autoimmune diseases (ADs) and interstitial cystitis/bladder pain syndrome (IC/BPS) has long been investigated. However, the lack of comprehensive descriptions of patients in the literature has made comparison and evaluation impossible. We aim to investigate the risk of systemic ADs in patients with IC/BPS in Taiwan using a population-based administrative database.Methods: This study evaluated 1,095 patients newly diagnosed with IC/BPS between 2000 and 2013, using data from Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Τhe trigger for the initial formulation of this theory was the epidemiological observation of existing similarities regarding the sex and age distribution of patients with PBS/IC compared to patients with other known autoimmune diseases. 11 , 13 The autoimmunity-based pathophysiological mechanism of PBS/IC was further supported by the clinical concordance found between PBS/IC and various autoimmune syndromes, and also by the fact that PBS/IC is considered as a manifestation of some systemic disorders, such as irritable bowel syndrome, migraine, anxiety, and depression. 14–16 In addition, the autoimmunity-based theory around PBS/IC pathophysiology was fueled by the fact that autoimmune-originating characteristics, including episodic symptom flare and a relapsing and/or treatment-refractory nature, are frequently present in PBS/IC patients.…”
Section: Autoimmunity: a Primary Suspect For Pbs/ic?mentioning
confidence: 89%
“…Τhe trigger for the initial formulation of this theory was the epidemiological observation of existing similarities regarding the sex and age distribution of patients with PBS/IC compared to patients with other known autoimmune diseases. 11 , 13 The autoimmunity-based pathophysiological mechanism of PBS/IC was further supported by the clinical concordance found between PBS/IC and various autoimmune syndromes, and also by the fact that PBS/IC is considered as a manifestation of some systemic disorders, such as irritable bowel syndrome, migraine, anxiety, and depression. 14–16 In addition, the autoimmunity-based theory around PBS/IC pathophysiology was fueled by the fact that autoimmune-originating characteristics, including episodic symptom flare and a relapsing and/or treatment-refractory nature, are frequently present in PBS/IC patients.…”
Section: Autoimmunity: a Primary Suspect For Pbs/ic?mentioning
confidence: 89%
“…However, in a nationwide population-based study evaluating the risk of autoimmune diseases in patients with IC, it was demonstrated that the odds of rheumatoid arthritis were 1.516 times higher and Sjogren's syndrome were 1.962 times higher. Interestingly, the authors found no increased risk of SLE and did not report any SSc-related outcomes due to the limited number of patients [15].…”
Section: Systemic Sclerosis and Interstitial Cystitismentioning
confidence: 93%
“…The autoimmune theory is supported in part by the idea that there is noticeable epidemiological overlap between patients with IC/BPS and other individuals with known autoimmune disease (16,17). Additional support was gained from the finding that in IC/BPS the bladder wall is infiltrated with increased inflammatory cells, such as mast cells, T lymphocytes, and eosinophils (18,19).…”
Section: Autoimmune Theory Of Ic/bpsmentioning
confidence: 99%